Layanan Bimbingan Klasikal Berbasis Masalah (IKMS) untuk Meningkatkan Perencanaan Karir pada Siswa SMA - Hanani, Azrina Khalwa; Habsy, Bakhrudin All; Fathira, Sheilawaty Arum (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
The most important aspect of career planning is a deep understanding of an individual's interests and talents. Knowing and understanding interests and talents can help individuals find appropriate advanced learning opportunities and jobs that match their interests and maximize their talents. When individuals pursue further studies or careers that suit their interests and talents, individuals tend to become more motivated, happier, and more productive in the process. Additionally, a better understanding of interests and talents can help individuals make better decisions regarding education and employment. Based on high school principles and the development problems of the younger generation, high school students are certainly required to be able to determine their education and career paths according to their interests and abilities, and here are several things that can be done to support this. Career guidancein schools corresponds to this phenomenon and represents classical guidance. The research we conducted was a qualitative library research method, which included searching, reading, understanding and analyzing various literature containing research findings related to the research carried out